Principal component methods to quantify skiing technique - Federolf, P.; Reid, R.; Gilgien, M.; Haugen, P.; Smith, G. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: Ski instructors and coaches assess a skier's technique in order to recommend how he or she may improve performance. This assessment is highly subjective and requires years of experience. A quantitative method to evaluate the whole body movement patterns of skiers would allow objective comparisons of individual skiing techniques and may lead to a better understanding of motion control in skiing. In this study, a method was developed to decompose the whole body movement patterns of skiing into a set of principal movements that can be used to quantitatively describe skiing technique. The method was applied to compare the individual skiing technique of six highly-skilled racers in slalom.